1997
DOI: 10.1038/bjc.1997.370
|View full text |Cite
|
Sign up to set email alerts
|

Physical and psychosocial outcomes in cancer patients: a comparison of different age groups

Abstract: Summary In a cross-sectional study, we investigated the relationship between age, physical health, social and economic resources, functional status, activities of daily living (ADL) and disease-related variables of 227 patients with cancer. Using multidimensional outcome measures we examined age differences in three age groups (< 45, 46-65, >65 years) and identified predictors of performing ADL. The results indicated that older patients have outcomes similar to those of younger patients. There were no signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
18
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 25 publications
(38 reference statements)
3
18
1
Order By: Relevance
“…Even though prior studies found to have psychological distress on lower side in older patients [27] but some studies do not found any association between age and psychological well being or distress [28][29]. However, in our study the older age was found to have increased distress on HADS (D) subscale may be due to impact of more extensive surgery or the side effects of chemotherapy or radiotherapy.…”
Section: Discussioncontrasting
confidence: 56%
“…Even though prior studies found to have psychological distress on lower side in older patients [27] but some studies do not found any association between age and psychological well being or distress [28][29]. However, in our study the older age was found to have increased distress on HADS (D) subscale may be due to impact of more extensive surgery or the side effects of chemotherapy or radiotherapy.…”
Section: Discussioncontrasting
confidence: 56%
“…the start of systemic chemotherapy, for the measurement of QoL. Greimel et al [33] could not demonstrate any interaction between co-morbidity and KPS in their analysis of 227 patients with cancer. In addition, they were unable to demonstrate an age-dependent decline in KPS.…”
Section: Discussionmentioning
confidence: 97%
“…This is in line with recommendations from the literature on outcome analysis in this patient group. 21,23,24,67 Some studies of head and neck cancer patients even indicate that younger age is a risk factor for physical dysfunction 57 or depression. 11,14 The factors studied explained a significant percentage of variance of the various domains of QOL after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…11,20,21 With regard to age, it is often assumed that elderly patients fare worse after treatment, but few data support this view. [21][22][23][24] Functional status, as measured with the Karnofsky performance status (KPS), 25 a reliable and valid instrument to assess the functional status of cancer patients, 26 has been shown to be positively correlated with QOL. 27,28 Last, psychologic status may profoundly influence physical functioning, symptom perception, and mood after treatment.…”
mentioning
confidence: 99%